2018
DOI: 10.5296/jse.v8i2.12767
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Types and the Cognitive - Metacognitive Strategies

Abstract: This study investigates the relationship between the personality type and cognitive-metacognitive strategies utilized by test-takers in reading comprehension tests. One hundred undergraduate Iranian English Foreign Learning (EFL) students participated in a reading comprehension test followed by a questionnaire and the Myers & Briggs Type Inventory. The questionnaire consisted of 30 cognitive-metacognitive items (Phakiti, 2003). These questions inquired about the thought process that occurred while completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
4
0
2
Order By: Relevance
“…Dragoni and his colleagues (2011) found a highly positive correlation between executives' cognitive abilities (similar to personality traits) and their strategic thinking competency. In a similar study, Soleimani et al (2018) found that there is a relationship between MBTI personality type of undergraduate students and their cognitive-metacognitive strategies usage in a reading comprehension test. Davidz and Nightingale (2008) showed that participants' personality characteristics positively affect the development of systemic thinking.…”
Section: Flexibility (F)mentioning
confidence: 80%
“…Dragoni and his colleagues (2011) found a highly positive correlation between executives' cognitive abilities (similar to personality traits) and their strategic thinking competency. In a similar study, Soleimani et al (2018) found that there is a relationship between MBTI personality type of undergraduate students and their cognitive-metacognitive strategies usage in a reading comprehension test. Davidz and Nightingale (2008) showed that participants' personality characteristics positively affect the development of systemic thinking.…”
Section: Flexibility (F)mentioning
confidence: 80%
“…They reported positive correlations between ST practices and the personality traits of participants. Using the same instrument, Soleimani et al [43] observed that there is a positive relationship between the PT of undergraduate students and their cognitive-metacognitive strategy usage in a reading comprehension exam. Therefore, we hypothesize the following.…”
Section: ) Hypothesis Developmentmentioning
confidence: 99%
“…Feist dan Feist (dalam Fatmawati & Khabibah, 2019) mendefenisikan kepribadian sebagai pola sifat dan karakteristik tertentu yang relatif permanen, baik konsistensi maupun individualitas pada perilaku seseorang. Dengan demikian, tipe kepribadian mengacu pada klasifikasi tipe individu secara psikologis, dimana terdapat preferensi seseorang dalam melakukan atau menentukan segala sesuatu dalam kehidupannya (Soleimani et al, 2018).…”
Section: Seminar Nasional Pembelajaran Sejarah (Snps Uns 2020)unclassified